The Process of War Disillusionment in Erich Maria Remarque’s All Quiet on the Western Front: A Freudian Perspective - Bayu Kusuma; AMBAR ANDAYANI (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the process of war disillusionment in Erich Maria Remarque’s All Quiet on the Western Front, tracing how the idealistic convictions instilled in its protagonist before enlistment collapse under the pressure of trench warfare. The analysis draws on Sigmund Freud’s concept of disillusionment, developed in Thoughts for the Times on War and Death (1915), which accounts for the erosion of confidence in moral progress and civilized authority once such convictions are contradicted by lived experience. Using a descriptive qualitative method within a psychological literary approach, textual evidence was gathered through close reading and interpreted through this Freudian lens. Two questions guided the inquiry: what causes war disillusionment in the novel, and how it becomes visible through the protagonist’s evolving consciousness. The findings indicate that disillusionment originates from four interlocking sources: the failure of trusted authority figures, direct exposure to death and violence, the disintegration of civilizational and institutional ideals, and a widening psychological rupture from a pre-war identity. This disillusionment is expressed through the collapse of moral and patriotic conviction, a progressive narrowing of emotional responsiveness, an estrangement from a former self, and the disappearance of any coherent vision of the future. The study concludes that war disillusionment unfolds as an accumulating psychological transformation rather than a single rupture, reshaping how the individual understands identity, morality, and human existence.